2020
DOI: 10.3390/molecules25071542
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphism of GSTP-1 Affects Cyclophosphamide Treatment of Autoimmune Diseases

Abstract: Cyclophosphamide is one of the most potent and reliable anti-cancer and immunosuppressive drugs. In our study, 33 individuals with different autoimmune diseases were treated with cyclophosphamide according to standard protocols. The responses to the treatments were determined by measuring the alteration of several typical parameters characterizing the given autoimmune diseases over time. We concluded that about 45% of the patients responded to the treatment. Patients were genotyped for polymorphisms of the CYP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Cyclophosphamide, as an immunosuppressant, is widely used in the treatment of various autoimmune diseases. 16 In addition, cyclophosphamide has an important role in antitumor and anticancer therapy, and its therapeutic effect is partly attributed to the stimulation of the body's immune response. 17 However, cyclophosphamide causes damage to the intestinal immune barrier and increases intestinal permeability, which in turn leads to gut microbiota disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclophosphamide, as an immunosuppressant, is widely used in the treatment of various autoimmune diseases. 16 In addition, cyclophosphamide has an important role in antitumor and anticancer therapy, and its therapeutic effect is partly attributed to the stimulation of the body's immune response. 17 However, cyclophosphamide causes damage to the intestinal immune barrier and increases intestinal permeability, which in turn leads to gut microbiota disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical outcome of this study was in line with that of our study to some extent in spite of the fact that they failed to perform the prognosis analysis. 31 And another retrospective study initiated by Yuan et al investigated the association of GSTP-1 and clinical outcome of gemcitabine-cisplatin chemotherapy in Chinese patients with NSCLC. 32 And the results suggested that A genotype carriers were significantly higher in sensitive group than in non-sensitive group, which was consistent with our study as well.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study of 70 patients with proliferative lupus nephritis treated with cyclophosphamide showed that the 105 Ile/Val GSTP1 genotype was an independent predictor of poor renal outcome and that the GSTM1 null genotype was the only factor to affect the incidence of adverse effects (Audemard-Verger et al, 2016). Conversely, in a study of The Nitrogen Mustards 33 patients with a variety of autoimmune conditions treated with cyclophosphamide, those with the 105 Ile/Val GSTP1 variant had a higher response rate (Hajdin ak et al, 2020). In another study, the 105 Ile/Val GSTP1 and the 105 Val/Val GSTP1 genotypes increased the risk of short-term toxicity with pulsed high-dose cyclophosphamide in patients with SLE (Zhong et al, 2006).…”
Section: B Pharmacogenomicsmentioning
confidence: 99%